Influence of restoration height and masticatory load orientation on ceramic endocrowns - da Fonseca, Gabriela F. [UNESP]; Dal Piva, Amanda M.O. [UNESP]; Tribst, João P.M. [UNESP]; Borges, Alexandre L.S. [UNESP] (Jaypee Brothers Medical Publishing, 2018)
Aim: Endocrown restorations are an alternative to restore endodontically treated teeth. Due to the fact that in the literature it is recommended a remnant of 1.5 mm, different heights of endocrown were elaborated and analyzed, obtaining possible faults and their location. This study aimed to evaluate the mechanism of stress distribution in the tooth/restoration set, varying two factors: restoration height-three levels, and load application-two levels (oblique or axial), totaling six groups. Materials and methods: For finite element analysis (FEA), a maxillary premolar was modeled with an endodontic treatment. Then, this template was triplicated and each copy received an endocrown restoration of different heights: G6 (4.5 mm), G7 (5.5 mm), and G8 (6.5 mm). The models were exported in STEP format to analysis software (ANSYS 17.2, ANSYS Inc.). During preprocessing, the solids were considered isotropic, linearly elastic, and homogeneous. Initially, a load (300 N) was axially applied in the central fossa region. For a second evaluation, an oblique load (300 N) was applied on the grinding slope of functional cusp. System fixation occurred at the base of polyurethane cylinder. Results were evaluated through maximum principal stress (MPS). Results: For axial load, lower stress values were generated in all groups. For oblique load, G8 showed a higher stress concentration in the cement layer and root dentin. Conclusion: When an endocrown restoration is performed, there is a tendency of failure in the cement line and in the root directly proportional to its size. However, regardless of the size of the element to be reconstituted, the axial direction of the masticatory loads tends to decrease stress concentration. Clinical significance: When performing an endocrown restoration, care must be taken with its high regardless the tooth remnant high, altering even the anatomical angulations of the occlusal face, when necessary, to avoid stress concentration in thick areas.
Keywords: Dental restoration failure; Dental stress analysis; Finite element analysis